Strengthening the Profile of Pancasila Students Through the Theme of Local Wisdom in Building the Character of Elementary-Level Students - Nurmala, Sinta; Maulida, Utami (CV Kalimasada Group, 2024)
Strengthening the profile of Pancasila Students is a government initiative embedded in the Merdeka Curriculum to enable students to recognize Indonesia's local wisdom through traditional clothing, dances, musical instruments, games, and traditional cuisine. The purpose of this study is to comprehensively examine the strengthening of the Pancasila Student profile with the theme of local wisdom in character building. This research employs a qualitative descriptive approach to provide an in-depth discussion on character development through the Pancasila Student profile strengthening program implemented at Sekolah Dasar Negeri Gondrong 7 in Tangerang City. The findings aim to elaborate on the strengthening of the Pancasila Student profile as a medium for shaping elementary students’ character, ensuring the program’s meaningful implementation and fostering positive character traits in young learners. The implementation of the Pancasila Student profile strengthening program, themed on local wisdom, at SDN Gondrong 7 has proven effective in building students' character through core values. These values include religious devotion, independence, hard work, responsibility, curiosity, discipline, and social care. Through a series of processes and stages in local wisdom activities, the program is expected to instill these values consistently into students’ daily lives.